Impact of the pay-for-performance program on lower extremity amputations in patients with diabetes in Taiwan - Sheen, Yi-Jing (Medicine (Baltimore), 2018)
Patients with diabetes are at a high risk of lower extremity amputations and may have a reduced life expectancy. Taiwan has implemented a diabetes pay-for-performance (P4P) program providing team care to improve the control of disease and avoid subsequent complications. Few studies investigated the effects of adopting a nationalized policy to decrease amputation risk in diabetes previously. Our study aimed to analyze the impact of the P4P programs on the incidence of lower extremity amputations in Taiwanese patients with diabetes. This was a population-based cohort study using the Taiwan National Health Insurance Research Database (which provided coverage for 98% of the total population in Taiwan) from 1998 to 2007. Patients with diabetes were identified based on the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM) diagnostic codes. We linked procedure codes to inpatient claims to identify patients hospitalized for nontraumatic lower extremity amputations. A total of 9738 patients with diabetes with amputations were enrolled (mean age ± standard deviation: 64.4 ± 14.5 years; men: 63.9%). The incidence of nontraumatic diabetic lower extremity amputations decreased over the time period studied (3.79–2.27 per 1000 persons with diabetes). Based on the Cox proportional hazard regression model, male sex (hazard ratio: 1.83, 95% confidence interval [CI] 1.76–1.92), older age, and low socioeconomic status significantly interact with diabetes with respect to the risks of amputation. Patients who did not join the P4P program for diabetes care had a 3.46-fold higher risk of amputation compared with those who joined (95% CI 3.19–3.76). The amputation rate in Taiwanese diabetic patients decreased over the time period observed. Diabetes in patients with low socioeconomic status is associated with an increased risk of amputations. Our findings suggested that in addition to medical interventions and self-management educations, formulate and implement of medical policies, such as P4P program, might have a significant effect on decreasing the diabetes-related amputation rate.